Pengaruh Massage Counterpressure Terhadap Penurunan Nyeri Ibu Post Sectio Caesarea di RSU Kabupaten Manokwari - Sestu Iriami Mintaningtyas; Yuni Subhi Isnaini (Universitas Malahayati Lampung, 2023)
ABSTRACT Delivery by sectio caesarea (SC) is the act of dividing the mother's abdomen with an incision to remove the baby. SC surgery causes pain in the incision area which occurs due to changes in tissue continuity and will gradually recover over 6 weeks, while recovery from numbness, soreness or itching around the wound can last up to 6 months. Non-pharmacological methods in pain management aim to shorten the intensity of pain, one of the methods in reducing post sectio caesarea pain is by means of Counterpressure Massage. The purpose of this study was to evaluate the effect of Counterpressure Massage on reducing post-sectio caesarea maternal pain at the Manokwari District Public Hospital. This study analyzes the intensity of pain after being given a Counterpressure Massage. This type of research is a quasy experiment with a research design of One group Pre-post test with control group. The sample in this study was Mrs. Post Sectio Caesarea in the working area of the Manokwari Regency Public Hospital with 32 respondents using Acidental Sampling. This study conducted an analysis before and after being given a Counterpressure Massage intervention with a duration of 15-20 minutes carried out for 3-4 days according to the SOP for Massage Counterpressure. The research instrument used was the Numeric Rating Scale (NRS) questionnaire. The data taken is primary data and data analysis using parametric and non-parametric tests. The results showed that there were differences in pain intensity scores before and after treatment in the intervention group with a p value α value (0.05). The conclusion is that Counterpressure Massage has an effect on reducing pain intensity in post sectio caesarea mothers after being given intervention. Keywords: Mother Post Sectio Caesarea, Pain Intensity, Counterpressure Massage ABSTRAK Persalinan secara sectio caesarea (SC) merupakan Tindakan pembelahan abdomen ibu dengan irisan untuk mengeluarkan bayinya. Tindakan operasi SC menimbulkan nyeri di daerah luka insisi yang terjadi karena perubahan kontinuitas jaringan dan akan berangsur pulih selama 6 minggu, sedangkan pemulihan masalah kebas, pegal atau gatal disekitar luka dapat berlangsung sampai 6 bulan. Metode non farmakologi dalam penanganan nyeri bertujuan untuk mempersingkat intensitas nyeri, salah satu metode dalam pengurangan nyeri post sectio caesarea yaitu dengan cara Massage Counterpressure. Tujuan dari penelitian ini adalah untuk mengevaluasi pengaruh Massage Counterpressure terhadap penurunan nyeri Ibu post sectio caesarea di RSU Kabupaten Manokwari. Penelitian ini melakukan analisis intensitas nyeri setelah diberikan Massage Counterpressure. Jenis penelitian ini adalah quasy experiment dengan rancangan penelitian One group Pre-post test with control group.sampel dalam penelitian ini adalah Ibu Post Sectio Caesarea yang berada di wilayah kerja RSU Kabupaten Manokwari sebanyak 32 responden dengan Teknik pengambilan sampel menggunakan Acidental Sampling. Penelitian ini melakukan analisis sebelum dan setelah diberikan intervensi Massage Counterpressure durasi 15-20 menit dilakukan selama 3-4 hari sesuai SOP Massage Counterpressure. Instrument penelitian yang digunakan adalah kuesioner Numeric Rating Scale (NRS). Data yang diambil merupakan data primer dan Analisa data menggunakan uji parametrik dan non parametrik test. Hasil penelitian menunjukkan bahwa terdapat perbedaan skor intensitas nyeri sebelum dan sesudah perlakuan pada kelompok intervensi dengan nilai p value nilai α (0,05). Kesimpulan yaitu Massage Counterpressure berpengaruh terhadap penurunan intensitas nyeri pada ibu post sectio caesarea setelah diberikan intervensi. Kata Kunci : Ibu Post Sectio Caesarea, Intensitas Nyeri, Massage Counterpressure